Avian Influenza (AI) is well known as Avian flu, Fowl pest, Fowl plaque, or Flu burung, caused by influenza virus type A. This virus is belonged to Orthomyxoviridae and could infect many kind of species such as bird, pig, horse, cat, as well as human. Vaccination is applied to control the disease using inactivated vaccine, which induced the specific antibody against H5 antigen. Passive immunization using specific antisera against H5 antigen is thought to be usefull in controlling the disease - Andrijanto H. Angi; I Wayan Teguh Wibawan; Sri Murtini (Forum Pasca Sarjana, 2009)
Avian Influenza (AI) is well known as Avian flu, Fowl pest, Fowl plaque, or Flu burung, caused by influenza virus type A. This virus is belonged to Orthomyxoviridae and could infect many kind of species such as bird, pig, horse, cat, as well as human. Vaccination is applied to control the disease using inactivated vaccine, which induced the specific antibody against H5 antigen. Passive immunization using specific antisera against H5 antigen is thought to be usefull in controlling the disease especially in the treatment of infected host. In this experiment the neutralization ability of specific antisera against H5 were studied using various field viral isolates subtype H5N1. Antisera was developed in Cavia porcellus which vaccinated with AI subtype H5N1 in activated vaccine. The titre of antisera obtained is 28 used HI test. Four AI virus subtype H5N1 isolates from 2003 to 2006 agains viral were we as tested virus. The neutralization test showed that the sera were able to neutralizing 10 4 EID50 AI virus H5N1 with neutralization index range of 1.1-1.3. The result indicated that the specific antisera had the neutralization potency to the field virus. Key words: avian influenza, neutralization test, neutralization index